2001
DOI: 10.1097/00000539-200105000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of NMDA Receptor Function by Ketamine and Magnesium. Part II: Interactions with Volatile Anesthetics

Abstract: Clinically relevant concentrations of volatile anesthetics inhibit functioning of N-methyl-D-aspartate receptors expressed recombinantly in Xenopus oocytes. This inhibition is reversible, concentration-dependent and voltage-insensitive, and results from noncompetitive antagonism of glutamate/glycine signaling. In addition, these effects can be potentiated significantly by co-application of either Mg2+, S(+)-ketamine, or--most profoundly--both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(102 citation statements)
references
References 24 publications
8
92
0
2
Order By: Relevance
“…9 Moreover, several in vitro electrophysiological and pharmacological studies have demonstrated sevoflurane's anti-NMDA properties. 21,23 The findings from our study suggest that sevoflurane, when administered at concentrations even below the MAC value, might play an anti-hyperalgesic role via an anti-NMDA action.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…9 Moreover, several in vitro electrophysiological and pharmacological studies have demonstrated sevoflurane's anti-NMDA properties. 21,23 The findings from our study suggest that sevoflurane, when administered at concentrations even below the MAC value, might play an anti-hyperalgesic role via an anti-NMDA action.…”
Section: Discussionmentioning
confidence: 71%
“…8,[18][19][20] Halogenated anesthetics have in vitro anti-NMDA properties. [21][22][23][24] Other studies have shown that halogenated anesthetics induce hyperalgesia when administered at very low concentrations 25,26 and even decrease morphine analgesic effects. 25,27 However, in the context of current clinical practice, it is unresolved as to whether or not inhaled anesthetics elicit residual effects on postoperative hyperalgesia.…”
Section: Résumémentioning
confidence: 99%
“…This may explain lower effectiveness of pethidine in opioid-dependent patients compare to normal population. Ketamine has also effect on modulation of NMDA receptor function to decrease tolerance to opioids in opioid-dependent patients (Hollmann, Liu, Hoenemann, Liu, & Durieux, 2001). However, ketamine effect on postoperative shivering is not far more than clonidine or Pethidine in opioid-dependent patients.…”
Section: Resultsmentioning
confidence: 99%
“…(5) Bu amaçla, NMDA reseptör antagonizması yoluyla SSS'de depresyon yaparak anestezik etkinlik gösteren magnezyum sülfat, son yıllarda genel anestezi uygulamalarında adjuvan olarak kullanıl-maya başlanmıştır. (1) Magnezyumun in vitro şartlarda adrenerjik sinir uçları ve adrenal bezlerden katekolamin salınımını inhibe etmesi, insanlarda da katekolamin salınımını inhibe edebileceğini düşündürmüştür. James ve ark.…”
Section: Discussionunclassified